(untitled) (Medico Legal Update, 2020)
Multiple myeloma (MM) still an incurable disease that require better recognition and more research. Many previous studies shown the interaction between myeloma cells and bone marrow stromal cells for the initiation and progression of multiple myeloma . Many chemokines and their receptors including interleukin-6 (IL-6) an play important roles in this interaction. The main purpose of this study is assess the serum level of IL-6 and Lactate dehydrogenase on stage-III of MM patients and healthy controls then Finding the correlation with creatinine and calcium levels. Serum level of IL-6 , Lactate Dehydrogenase , creatinine and calcium levels of (30) MM patients diagnosis at stage –III according to International staging System (ISS) were measurement. The results for these parameters compare with (30) age- and sex-matched healthy controls groups. The results were showed that the mean levels of IL-6 , Lactate dehydrogenase , creatinine and calcium (increased or decreased)high significant (p?0.001) when compared with healthy controls . The results of the study suggested the important role of chemokines including IL-6 in the progression of the disease and its relationship with some biochemical parameters , especially in the stage-III of the disease.